Assessing quality of web sites based on multimedia content - Prudhvi Kolla, Naga; JKR Sastry, Dr; V Chandra Prakash, Dr; Krishna Onteru, Siva; Surya Pinninti, Yeshwanth (International Journal of Engineering and Technology, 2018)
Information is being presented these days in terms of text, data, images, video, and audio. Graphics and animations. Information is being disseminated through web sites which are either dynamic or static. Quality of the WEB site is however a big question. Users are quite concerned about quality of the WEB site. Too many operations if need to be undertaken for want of quality visualisation of the content such as Images, then the users loose interest in looking at that kind of content. WEB sites are presenting the content by integrating text and data with multimedia objects. Quality visualisation of the multimedia content would be the real issue as presenting these elements. The number of operations that the user is expected to carry must be minimised as much as possible.Quality presentation of the multimedia objects is most important for making available web sites to the customer satis-faction. Assessment of quality of the multimedia objects is needed to project the extent to which the users will be satis-fied with a web site that hosts different types of multimedia objects. In this paper the methods that computes quality of multimedia objects individually and also considering all types of multi-media objects as a whole are presented.Â Â
Keywords: Quality of WEB Sites; Quality Assessment Framework; Quality of Multimedia Objects; Quality Assessment of Multimedia Objects.